Greenhouse gas emissions and carbon and nitrogen stock in different forage production systems - Cremostim, Beatriz Elisa Bizzuti (2024)
Plant biodiversity in grazing lands is reported to increase productivity and soil health compared to monocultures, as well as change carbon, nitrogen stocks, and greenhouse gas emissions. This comprehensive study explores the effects of including shrubs (silvopastoral) and leguminous forages (grass-legume) in the grazing system, exploring the impacts of these systems on greenhouse gas (GHG) emissions, soil quality, and soil biological activity. Two experiments were conducted. Experiment 1 was in southeastern Brazil evaluating the effects of exclusive grass systems (EGS) and silvopastoral systems (SPS) incorporating Tithonia diversifolia in GHG emissions, emission intensity, soil carbon (C) and nitrogen (N) stock, organic matter fractionation, and isotopic composition. While cumulative GHG emissions were comparable, emission intensity was lower in SPS. No significant differences were found in carbon and nitrogen stocks, but a tendency for higher particulate organic carbon in SPS and a distinct carbon isotopic signature indicate T. diversifolia\'s influence on soil organic carbon levels despite the short-term establishment. Experiment 2, conducted at the North Florida Research Education Center NFREC in Mariana, Florida, USA, assessed soil biological activity (STBA), C mineralization, and 13CO2 in contrasting grazing systems 10 years old. The treatments included bahiagrass (Paspalum notatum Flugge) with nitrogen fertilizer (BGN), bahiagrass (BG) with a winter legume in the cool season, and bahiagrass with perennial rhizoma peanut (Arachis glabrata Benth.) and a winter legume (BGRP).Soil cumulative CO2 emission, soil-test biological activity, and carbon mineralization were not different among treatments. Even though BGRP reduced carbon and nitrogen stocks, it exhibited biological activity comparable to that of the other treatments, BG and BGN.. Incorporating legume forage into grassland systems emerges as a significant alternative to reduce the need for nitrogen fertilizer without impacting soil biological activity. These experiments highlight the complex interplay between land management practices, and C4/C3 integration in grazing systems, emphasizing the need for more studies to fully understand the potential of sustainable agricultural systems in mitigating climate change and optimizing soil health.